2009
DOI: 10.1007/s00280-009-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of folate levels after leucovorin administration in colorectal cancer

Abstract: The expression level of FPGS, GGH and ABCC1 in CRC tissues could predict the reduced folate level after LV administration, and these factors may determine the efficacy of LV treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…Indeed, high expression of FPGS and low expression of GGH seem to be predictive for high levels of reduced folates after LV administration in colorectal cancer (23). However, in the present study, neither FPGS nor GGH gene expression correlated significantly with DFS, after correction for multiple testing.…”
Section: Ggh) and Folate Metabolism (Aldh1l1 Aldh1l2 Amt Atic Ftccontrasting
confidence: 55%
See 1 more Smart Citation
“…Indeed, high expression of FPGS and low expression of GGH seem to be predictive for high levels of reduced folates after LV administration in colorectal cancer (23). However, in the present study, neither FPGS nor GGH gene expression correlated significantly with DFS, after correction for multiple testing.…”
Section: Ggh) and Folate Metabolism (Aldh1l1 Aldh1l2 Amt Atic Ftccontrasting
confidence: 55%
“…The ABCC1 and ABCC3 proteins are members of the superfamily of adenosine triphosphate (ATP)-binding cassette (ABC) transporters that transfer a variety of molecules, including monoglutamated forms of reduced folates, to the outside of the cell membrane (8). Based on recent publications, the ABCC1 protein seems to be a promising predictive factor for reduced folate levels after LV administration (23). However, in the present study, expression of the ABCC1 gene did not correlate with DFS, nor did expression of the ABCC3 gene.…”
Section: Ggh) and Folate Metabolism (Aldh1l1 Aldh1l2 Amt Atic Ftcmentioning
confidence: 99%
“…Therefore, the absence/presence of LV may affect predictive factors, such as folate-related genes. Actually, we previously reported that the gene expression levels of folylpolyglutamate synthase (FPGS) and gamma-glutamyl hydrolase (GGH) in tumors could predict the levels of reduced folate after LV administration in tumor tissue [23]. Moreover, we have reported that a reduction in GGH gene expression was associated with the response to UFT/LV chemotherapy in patients with colorectal cancer [24].…”
Section: Discussionmentioning
confidence: 88%
“…We previously reported that the tumor expression levels of folate-related genes, such as folylpolyglutamate synthase (FPGS) and gamma-glutamyl hydrolase (GGH), and of 5-FU-related genes, such as thymidine phosphorylase (TYMP), thymidylate synthetase (TYMS), and dihydropyrimidine dehydrogenase (DPYD), are closely correlated with the response to preoperative chemotherapy or chemoradiotherapy including UFT or S-1 [8,[22][23][24]. Since the most substantial difference between these two 5-FU-based chemotherapies, i.e., UFT/LV and S-1, is the presence/ absence of LV, the predictive factors may differ when UFT/ LV and S-1 are used for CRT.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the amount of mRNA collected from the tissues was too small to examine in some cases. For FPGS, Sadahiro et al [32] reported that its expression level might determine the efficacy of leucovorin treatment, but there have been few reports about the role of FPGS in colorectal cancer. Further assessment of REG4 and FPGS in larger prospective trials is thus needed.…”
Section: Discussionmentioning
confidence: 98%